Pengaruh Pemberian Tumis Daun Pepaya terhadap Kelancaran Produksi ASI pada Ibu Nifas di TPMB IS Kabupaten Bogor - Yenny Aulya; Andi Julia Rifiana; Santi Eriska (Jurnal Akademika Baiturrahim Jambi, 2023)
The achieving exclusive breastfeeding is difficult because breastfeeding is not smooth. This problem meant that no one could breastfeed the baby, which made breastfeeding difficult. According to the West Java Health Office, exclusive breastfeeding in Bogor City has only reached 49.95%, while exclusive breastfeeding in Bogor Regency is 45.52%, which means that exclusive breastfeeding is very low. Non-pharmacological treatment of breastfeeding can be done by giving papaya leaf vegetables. Knowing the effect of stir-fried papaya leaves on the smooth running of breast milk in puerperal mothers at TPMB IS Bogor Regency in 2022.Quasi experiment with pretest posttest approach total sample of 40 respondents. The sampling technique uses total sampling. Instruments in the study used observation sheets. Data analysis uses paired t-test to determine the effect and Wilxocon test to determine the difference in the smooth production of breast milk. The average level of smoothness of breast milk before and after sautéing papaya leaves is 1.35 and 5.85. Wilxocon test results obtained a p value of 0.000 < 0.05. There is an influence of stir-frying papaya leaves on the smooth production of breast milk in postpartum mothers at TPMB IS Bogor Regency 2022. Puerperal mothers can consume sautéed papaya leaves to facilitate breast milk production